Antecedents of turnover intention in China's township and village enterprises - Ma, Xiao Wei (2006)
This is a cross-sectional study to examine the relationship between the dependent variable---turnover intention and three sets of independent variables: demographic factors including age, organizational tenure and income; controllable factors including job satisfaction (with pay, recognition, and supervision), organizational commitment and organizational citizenship behaviors; and uncontrollable factors including perceived alternative employment opportunity and job-hopping. Another objective of this study is to find the extent to which the controllable factors and uncontrollable factors are related to the turnover intention, and give an answer to the question--whether the turnover is controllable or uncontrollable in China's TVEs. A total of 143 employees from EDCH (Economy Development Complex in HeBei Province, China) were involved in this study. The questionnaire in this research paper was constructed based on extensive literature review. The whole data analyses and hypothesis testing in this paper were analyzed using Statistical Package for the Social Sciences (SPSS). The research discovered that demographic factors including age, organizational tenure and income do not have negative and significant relationship with turnover intention; that controllable factors including job satisfaction (with pay, recognition, supervision), organizational commitment, and organizational citizenship behavior were negatively and significantly related to turnover intention; that one uncontrollable factor --- perceived alternative employment opportunity really has positive and significant relationship with turnover intention, but the other uncontrollable factor---job hopping was not found having significant relationship with turnover intention, and that in EDCH, most of the employee turnover is controllable and with regard to the turnover intention, the controllable factors explain more than the uncontrollable factors.